Optimization of Business Processes to Improve the Efficiency of Company Management in the International Market - Zhijie Huang; Robert Voskerichyan (Communications of International Proceedings, 2021)
For the success of the company both in the domestic and overseas market is product and marketing. Companies need to focus not only on customer retention, but also on product quality. A process-oriented approach in management can come to the aid of companies, when the management of an organization moves from managing individual resources and functional units to managing business processes that link together the activities of all structures of the company. Practice shows that effective management of the company's activities in the restaurant business is directly related to the constant improvement and implementation of new technologies, the development of new products and services, marketing promotion, which should correspond to the continuous improvement of business processes, and is related to the strategy of the company itself [1]. In this situation, the issue of research and improvement of business processes in the restaurant business becomes especially relevant. At the same time, it should be taken into account that a necessary condition for the effective operation of a company and increasing its competitiveness is not only the consistent implementation of business processes, but also their objective assessment.
Keywords: Business Processes; Restaurant Business; International Environment; New Technologies; Competitiveness.